2020
DOI: 10.1159/000507226
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics to Prevent Relapse of Adjustable Gastric Balloon Hyperinflation: Feasible for Balloon Maintenance?

Abstract: The placement of an intragastric balloon (IGB) plays an increasingly important role in the treatment of obesity. The authors describe the cases of 2 female patients, 34 and 62 years old, who were submitted to the implantation of a Spatz3® IGB to treat obesity. Ten to fourteen weeks later, the patients presented complaints of epigastric pain, vomiting, and abdominal distension. A bulging of the upper abdominal wall was noticed upon physical examination. Upper gastrointestinal endoscopy confirmed the clinical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…A total of 10 publications (11 cases) [ 15 , 23 31 ] describing spontaneous IGB hyperinflation were identified in the literature despite a reported rate of approximately 2% in post-marketing studies [ 13 ]. All identified cases shared a common definition of spontaneous IGB hyperinflation which is consistent with the FDA’s statement [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 10 publications (11 cases) [ 15 , 23 31 ] describing spontaneous IGB hyperinflation were identified in the literature despite a reported rate of approximately 2% in post-marketing studies [ 13 ]. All identified cases shared a common definition of spontaneous IGB hyperinflation which is consistent with the FDA’s statement [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, our systematic review of literature identified multiple case studies reporting asymptomatic microbial colonization of the IGB without balloon hyperinflation [ 41 , 44 , 45 ]. In contrast, others described bacterial or fungal colonization with associated symptomatic spontaneous balloon hyperinflation [ 25 , 27 29 , 31 ]. In combination with the results of our experiment, these observations suggest that IGB contamination and ensuing microbial fermentation may not be the sole cause of hyperinflation, and the presence of additional factors is likely involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 publications (11 cases) [15,[23][24][25][26][27][28][29][30][31] describing spontaneous IGB hyperin ation were identi ed in the literature despite a reported rate of approximately 2% in post-marketing studies [13]. Patient baseline characteristics, type of IGB, clinical presentation and subsequent management are detailed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism of hyperinflation, in this case, is unclear. Previous reports have found contamination of the IGB fluid with gas-forming micro-organisms like some species of Candida and Streptococcus viridans [ 11 - 12 ]. The fluid used in these balloons is sterile and so authors have proposed that the integrity of the balloon can be compromised and become permeable [ 13 ].…”
Section: Discussionmentioning
confidence: 99%